Practical augmented reality : a guide to the technologies, applications, and human factors for AR and VR - Aukstakalnis, Steve (Addison-Wesley, 2017)
This is the most comprehensive and up-to-date guide to the technologies, applications and human factors considerations of Augmented Reality (AR) and Virtual Reality (VR) systems and wearable computing devices. Ideal for practitioners and students alike, it brings together comprehensive coverage of both theory and practice, emphasizing leading-edge displays, sensors, and other enabling technologies and tools that are already commercially available or will be soon.